Functional role of glycosphingolipids and gangliosides in control of cell adhesion, motility, and growth, through glycosynaptic microdomains - Regina Todeschini, Adriane; Hakomori, Sen-itiroh (Biochimica et biophysica acta, 2008)
At cell surface microdomains, glycosyl epitopes, carried either by glycosphingolipids, N- or O-linked oligosaccharides, are recognized by carbohydrate-binding proteins or complementary carbohydrates. In both cases, the carbohydrate epitopes may be clustered with specific signal transducers, tetraspanins, adhesion receptors or growth factor receptors. Through this framework, carbohydrates can mediate cell signaling leading to changes in cellular phenotype. Microdomains involved in carbohydrate-dependent cell adhesion inducing cell activation, motility, and growth are termed “glycosynapse”. In this review a historical synopsis of glycosphingolipids-enriched microdomains study leading to the concept of glycosynapse is presented. Examples of glycosynapse as signaling unit controlling the tumor cell phenotype are discussed in three contexts: (i) Cell-to-cell adhesion mediated by glycosphingolipids-to-glycosphingolipids interaction between interfacing glycosynaptic domains, through head-to-head ( trans) carbohydrate-to-carbohydrate interaction. (ii) Functional role of GM3 complexed with tetraspanin CD9, and interaction of such complex with integrins, or with fibroblast growth factor receptor, to control tumor cell phenotype and its reversion to normal cell phenotype. (iii) Inhibition of integrin-dependent Met kinase activity by GM2/tetraspanin CD82 complex in glycosynaptic microdomain. Data present here suggest that the organizational status of glycosynapse strongly affects cellular phenotype influencing tumor cell malignancy.